Academic Self-Efficacy as a Predictor of College Student’s Mental Health and Study Progress - Desi Yustari Muchtar; Zulfa Indira Wahyuni; Farhanah Murniasih; Amora Fatha Rasaki (‎‎‎TAZKIYA Journal of Psychology, 2023)
Mental health issues influenced college student's inner aspects, either emotionally, cognitively, physically, socially, and also their academic achievement. The ideal study period for college students is four years, but in fact, not all college students fulfill it. Academic self-efficacy had an essential role in determining mental health and study progress. The objective of this study was to measure the influence of academic self-efficacy on mental health and study progress. Three questionnaires The Mental Health Continuum-Short Form Scale and Academic Self Efficacy Scale were responded by 500 college students of UIN Syarif Hidayatullah Jakarta. The collected data was analyzed using the Multivariate Regression Analysis technique. The result found that academic self-efficacy had a positive influence on mental health and study progress significantly. Multivariate regression analysis technique uses SPSS and MPlus, where the dependent variable is more than one, namely study progress, a categorical variable with two categories (1 appropriate and 0 late) and the mental health variable is a continuum variable. The study found a significant positive impact of academic self-efficacy to study progress and mental health of college students of UIN Syarif Hidayatullah Jakarta. Academic self-efficacy had a .137 significance parameter to study progress and a .520 significance parameter to mental health. This result indicated that the higher academic self-efficacy level of college students would impact to the highest of their mental health and better study progress.